If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 4E + 6x + 1E + 8 Reorder the terms: 0 = 8 + 4E + 1E + 6x Combine like terms: 4E + 1E = 5E 0 = 8 + 5E + 6x Solving 0 = 8 + 5E + 6x Solving for variable 'E'. Move all terms containing E to the left, all other terms to the right. Add '-5E' to each side of the equation. 0 + -5E = 8 + 5E + -5E + 6x Remove the zero: -5E = 8 + 5E + -5E + 6x Combine like terms: 5E + -5E = 0 -5E = 8 + 0 + 6x -5E = 8 + 6x Divide each side by '-5'. E = -1.6 + -1.2x Simplifying E = -1.6 + -1.2x
| 3x-2=-3x | | 5x-15/2x-8 | | 4f-24+4f=-8-4 | | 8=d^2/3-1 | | 3x-4/10 | | x^2+64=x | | -6.4x=-4.8 | | 4c+8c=-54+3c | | -x+4x=-16+26x | | 24x+8=14x-6 | | cotx/sinx(secx-cosx)=1 | | 6=0.8*-4 | | 6(c-4)=48 | | 18-10x=-2 | | 8y=7x+8solvex | | 8-10x=-2 | | (2x^4-7x^3-5x+18)-(9x^3-7x+5)=0 | | 5x=2x+16 | | 8x-(5x-8)=3+2x | | 7(x+1)-4(x+3)=x-19 | | 5(k-3)-7=3k-(2k-1) | | (3x+2)=(2x-5) | | Log(3)*(5x-1)=3 | | 2-(11/n)=-(5/n^2) | | x-1/3=x-7/7 | | 2(3+6x)-5=7(x+8) | | 1050+5y=1050 | | R(x)=x^3+2 | | x^2+6x=28 | | 20b-3b-2=0 | | 3+ln(x+2)=6 | | p(x)=x^2-1 |